Perbedaan Minat Wirausaha pada Mahasiswa Lima Universitas di Yogyakarta Dilihat dari Penggunaan Media Sosial - Charolin Dealola Mega Cahyani (Fakultas Ekonomi, Universitas Sanata Dharma Yogyakarta, 2020)
This study aims to find out whether the differences entrepreneurial interests in five university students Yogyakarta seen from the use of social media that include the intensity of use social media, the number of social media (number of accounts and number of types) and the types of social media that are most often used. In this research, researchers use 100 respondents who come from Gadjah Mada University, Sunan Kalijaga State Islamic University, Sanata Dharma University, Atma Jaya Yogyakarta University and Sarjanawiyata Tamansiswa University. The data collection technique used in this research is incidental sampling technique. The analysis technique used in this research is independent sample t-test and one way ANOVA. The results of this study indicate that there is no difference in the entrepreneurial interests in Yogykarta, judjing from the use of social media.